STRATEGI KOMUNIKASI RADIOGRAFER MELALUI MEDIA SOSIAL: STUDI PADA AKUN INSTAGRAM PERHIMPUNAN RADIOGRAFER INDONESIA (PARI) - Dessy Kushardiyanti; Syaifudin Ramadhan Hidayat (Perhimpunan Radiografer Indonesia (PARI), 2022)
ABSTRACT BackBackground: The increasing number of social media users is currently being used by various sectors, including the health sector, which since the Covid-19 pandemic has received special attention from the public as ammunition for credible information. One of them is the Radiotherapy unit through various associations and or communities as an adhesive between radiographers. So far, Radioteapi has become a health unit that is safe in disseminating content information, no viral content has been found that contains negative content or violates the rules until it is in the name of the medical personnel in the Radiotherapy unit. This is certainly an opportunity to be used as a mediation of information in the health sector, especially through the association of medical personnel, one of which in this case is PARI. So, in the future, social media will not be limited only to the interests of members or radiographers but can be used as a manifestation of the radiographer's effective communication competence for the community. Methods: The research was conducted using a descriptive quantitative-qualitative approach with data collection methods in the form of literature studies, analysis of Instagram social media content, and interviews with PARI members. Convinience sampling was used to take samples of 2 central PARI Instragam accounts and 9 branch PARI Instagram accounts which were then processed by calculating engagement rate impressions and content strategy analysis with indicators like, comments and message content. Results: The results show that several central PARI Instagram accounts and branch managers have quite low engagement rate impressions, this can be improved by consistent content updates by considering the content strategy in the form of MEME content as entertainment as well as informative content, exposing members' experiences as positive reviews of the association, Documentation content of regular meeting activities and informative content of PARI membership updates. Conclusions: The content strategy that has been carried out at least meets the health indicators in the digital field according to a specific classification (Jean-Emmanuel Bibault, et all, 2017) in terms of reflective, responsive, relevant, and flexible information aimed at the target audience, namely between members and between radiographers. .